High input impedance voltage-mode universal filter and quadrature oscillator - Maheshwari S.; Mohan J.; Chauhan D.S. (My University, 2025)
A new single input and five outputs high input impedance voltage-mode universal biquadratic filter using three DVCCs, five passive components is presented. The proposed circuit offers the following features: high input impedance, realization of all the standard filter functions, that is, high-pass, band-pass, low-pass, band reject and all-pass filters simultaneously, the use of grounded capacitor, orthogonal control of ω0 and Q, no need to employ inverting type input signals, and no need to impose component choice except realizing the all-pass filter signal. A new quadrature oscillator circuit is also realized. PSPICE simulations using 0.35 μm TSMC CMOS parameters confirm the validity of the proposed circuit. © 2010 World Scientific Publishing Company.